Organic reaction mechanisms 2010 (Chichester, UK : John Wiley and Sons, 2012)
Organic Reaction Mechanisms 2010, the 46th annual volume in this highly successful and unique series, surveys research on organic reaction mechanisms described in the available literature dated 2010. The following classes of organic reaction mechanisms are comprehensively reviewed: Reaction of Aldehydes and Ketones and their Derivatives Reactions of Carboxylic, Phosphoric, and Sulfonic Acids and their DerivativesOxidation and Reduction Carbenes and Nitrenes Nucleophilic Aromatic SubstitutionEl.
Includes bibliographical references and indexes.
Print version record.
Keywords: Chemistry, Organic; SCIENCE -- Chemistry -- Organic; Chemistry, Organic; Electronic books; Electronic books